Evading strength and ductility trade-off in an inverse nacre structured magnesium matrix nanocomposite. (15th April 2022) - Luo, Xi; Zhao, Ke; He, Xu; Bai, Yuanli; De Andrade, Vincent; Zaiser, Michael; An, Linan; Liu, Jinling
Abstract: Mimicking nacre structure is an often-used strategy for developing materials which combine high strength and high toughness. Here, a novel strategy, named inverse nacre structure, is proposed where elongated and curled soft constituents are embedded in a matrix of hard constituent to form an ordered brick-and-mortar arrangement. This strategy is demonstrated in a particle reinforced metal matrix composite, using pure Mg as the soft phase and SiC nanoparticle reinforced Mg as the hard phase. The resulting nanocomposite yields high strength, and especially high tensile elongation which is five times that of the homogeneous counterpart. The superior comprehensive strengthening-toughening effect originates from the tailored inverse nacre structure which enables a stable microcrack-multiplication process by sufficiently promoting strain hardening so as to avoid any significant decrease in post-ultimate tensile strength. This strategy, while demonstrated here for the specific case of particle reinforced Mg, is not restricted to any particular material system but constitutes a generic pathway for the development of high-performance materials for engineering applications. Graphical abstract: Image, graphical abstract